APLIKASI RELIABILITY CENTERED MAINTENANCE (RCM) PADA SISTEM SALURAN GAS MESIN WARTSILA - Sunaryo Sunaryo; Legisnal Hakim; Denur Jumali (Jurnal Teknik Industri Terintegrasi, 2018)
Reliability Centered Maintenance (RCM) is a maintenance analysis method used to improve maintenance systems that focus on improving machine reliability. The problems that occur in the Wartsila machine at the Balipungut Duri Electricity Center is the frequent occurrence of machine failure that causes the low reliability of the machine. From the data of 2014-2016 years, a study of engine failure time in the line gas system that causes cessation of the machine. The study was carried out by FMEA treatment, damage rate and Weibull distribution data. The result of analysis shows that there is a critical component at Main gas admission valve that is at gas admission valve, admission valve filter and gas pipe feed. The rate of damage to the Main gas admission valve with the weibull distribution has a reduced rate of damage for b <1, of 0.010627 of this value can be known recommended treatment is Reactive / preventive maintenance and inpection maintenance.